Genomic profiles of Pyricularia oryzae in Sub-Saharan Africa: exploring population differences and their evolutionary implications in the region - Onaga, G.; Suktrakul, W.; Wanjiku, M.; Quibod, I.L.; Domelevo Entfellner, Jean-Baka; Bigirimana, J.; Habarugira, G.; Murori, R.; Asea, G.; Tella, H.E.; Amagnide, G.A.G.Y.; Zenna, N.; et al. (Frontiers Media, 2025)
Background: Rice blast, caused by Pyricularia oryzae (teleomorph: Magnaporthe oryzae), is one of the most economically damaging diseases affecting rice worldwide. While the evolutionary origins and genetic structures of Asian and European P. oryzae populations are relatively well characterized, African isolates remain underexplored. This knowledge gap impedes the development of informed management strategies for rice blast in the region. The present study was conducted to characterize the genetic origins, population structure, admixture, demographic history, and effector gene diversity of P. oryzae isolates in SSA, and to elucidate their evolutionary trajectories and implications for disease management.